Scleritis - Pavesio, Carlos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a concise but comprehensive overview of scleritis, with up-to-date information on all aspects, including diagnosis and treatment. Fundamental features of the pathogenesis of scleral inflammation are first discussed as a basis for understanding the therapeutic strategies. Detailed descriptions are then provided of clinical manifestations, the complications that can arise during the course of the disease process, and the best way to manage them. An individual chapter is devoted to infectious scleritis and its management, this being an uncommon but serious condition that may result not only in loss of vision but also in loss of the globe itself. The diagnostic approach to and various management options for scleritis are then discussed extensively, with coverage of local and systemic therapy and new strategies, including biologics. Apart from the potential impact on vision, inflammation of the sclera carries a risk of association with systemic diseases, some of which can prove fatal if not promptly recognized and managed. This book is designed to allow ophthalmologists to easily identify the condition and the signs indicative of a more severe problem. It will thereby assist in safe and effective management, and help in preserving vision and life.
General Considerations on Anatomy and Pathogenesis of Scleral Inflammation -- Classification and Clinical Presentations -- Associated Systemic Diseases -- Infectious Scleritis -- Diagnostic Approach to Scleritis -- Complications and their Management -- Management with Non-Steroidal Anti-Inflammatory Agents -- Management with Steroids: Local and Systemic -- Management with Immunosuppressive Therapy and Biologics. .
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology